Ground anchorages and anchored structures proceedings of the international conference organized by the Institution of Civil Engineers and held in London, UK, on 20-21 March 1997 - Littlejohn, G. S. (Thomas Telford, 1997)
This volume presents the proceedings of the first major international conference for over twenty years on the state-of-the-art of ground anchorage technology. Practical issues relating to construction and installation of anchorages are considered in a series of examples of engineering projects from around the world.